Understanding gait characteristics of Japanese elderly men through joint angle and angular velocity parameters - Afiah, Irma Nur; Nakashima, Hiroki; Loh, Ping Yeap; Muraki, Satoshi (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2022)
Studies investigating the walking patterns of elderly men are well documented, however, there has been no investigation of the gait parameters that specifically reflect the walking motion of elderly men. This study aimed to identify reliable gait parameters to represent the walking motion of elderly Japanese men. 33 elderly men (65 to 74.9 years old) and 20 very elderly men (greater than or equal to 75 years old) participated. A 3-dimensional motion analysis system was used to collect kinematic data and 52 gait parameters were analyzed namely; spatiotemporal gait, joint angle, and angular velocity parameters (peak value and peak timing at the hip, knee, and ankle joints. Our results showed that walking speed, cadence, walk ratio, gait cycle, peak joint angle timing, and angular velocity parameters significantly differ between elderly men and very elderly men. Delayed peak timing in the joint angle occurred during the terminal stance phase and pre-swing phase. The accurate parameters for walking motion in old Japanese men as they age may result from the peak timing of joint angle parameters and the peak value of angular velocity parameters.